Family experiences of inpatient mental health care for people with dementia - Wolverson, Emma L.; Harrison Dening, Karen; Dunning, Rebecca; Crowther, George; Russell, Gregor; Underwood, Benjamin R. (Frontiers in Psychiatry, 2023)
This study investigates family carers experiences of inpatient mental health care for people with dementia. A mental health inpatient admission for a person with dementia is usually considered when a person is distressed and this distress leads to behaviours that are assessed to be risky for the person or others. Participants included seven family carers whose relative with dementia had been cared for within a mental health ward in the United Kingdom within the last 5 years. Interviews were used to explore the circumstances that led to the admission, expectations of mental health care, and perceptions of care during the admission and support received by family carers. Participants described their distress at the time of admission and how the process of admission sometimes added to their distress. Carers often felt excluded from their relatives care in hospital and many felt a loss of their rights. Participants felt that the mental health admission had a negative impact on their relative with dementia. Mental health law and legislation was difficult to navigate and carers were concerned about how much knowledge and understanding of dementia staff have. Our findings suggest that family carers may benefit from targeted support during their relatives admission. Mental health wards could do more to recognise the expertise in care and knowledge of the person with dementia of family carers and involve them in planning care. More research is needed to explore the experiences and outcomes of people with dementia during such admissions.